Back isomerization from the excited state photoisomer of the laser dye 3,3' -diethyloxadicarbocyanine IODIDE (DODCI) - Scaffardi, Lucía Beatriz (1987)
The fluorescence of the first excited state of both the normal (N) and the photoisomer (P) forms of 3,3'-diethyloxadicarbocyanine iodide (DODCI) were analyzed under steady state conditions. Argon ion laser and argon ion pumped dye laser were used for excitation. The long wavelength fluorescence, belonging mainly to the P form, shows a similar degree of polarization as the short wavelength part arising from the N form. The fluorescence spectra of DODCI at different fluences and different wavelengths of laser excitation yielded information about the relative concentrations of the N and P forms. Photoequilibrium between the two species via the excited state of the P form is postulated. The rate constant estimated for the P★→N transition is much lower than the one expected from a model of a twisted state through which all the non-radiative transitions of the P form take place. The value is in agreement with that derived from the previous optoacoustic measurements exciting with higher fluences. The results indicate that stimulated emission and excited state absorption are not important under the conditions of the experiment.